Screening performance of Ultrasonographic B-lines in Detection of Lung Contusion following Blunt Trauma; a Diagnostic Accuracy Study - Abbasi, Saeed; Shaker, Hossein; Zareiee, Fariba; Farsi, Davood; Hafezimoghadam, Peyman; Rezai, Mahdi; Mahshidfar, Babak; Mofidi, Mani (Archives of Academic Emergency Medicine, 2018)
Introduction: Chest ultrasonography is routinely used in evaluation of chest trauma for diagnosis of pulmonary injury. This study aimed to evaluate the accuracy of B-Lines for diagnosing lung contusion in patients with blunt trauma of the chest. Methods: Trauma patients who met the inclusion criteria were enrolled in the study and underwent ultrasonography by trained emergency medicine residents. Ultrasound results were recorded in terms of number of B-lines and the existence of peripheral parenchymal lesion (PPL). After ultrasound, the patient underwent chest x-ray and chest CT scan (as reference test) and screening performance of B-lines and PPL were evaluated. Results: 147 patients underwent chest ultrasound. The mean age of the patients was 40.74 ± 18.6 (78.9% male). B-lines˃3 had 94.0% (95% CI: 83.45-98.75) sensitivity and 57.7% (95% CI: 47.3-67.7) specificity, B-lines˃6 had 90.0% (95% CI: 78.2-96.7) sensitivity and 93.81% (95% CI: 87.0-97.7) specificity, and PPL had 34.0% (95% CI: 21.2-48.8) sensitivity and 100% (95% CI: 96.3-100.0) specificity. Composite findings of B-lines˃6 + PPL had 92.0% (95% CI: 80.8-97. 8) sensitivity and 93.8% (95% CI: 87.0-97.7) specificity in the diagnosis of lung contusion. Conclusion: PPL and B-Lines˃6 had the highest accuracy in detecting lung contusion. B-Line˃6 had high sensitivity and specificity and was easy to perform; thus, it seems that B-Line˃6 could be considered as an alternative screening tool in detection of lung contusion.